(untitled) (Research, Society and Development, 2021)
The article was to report the creation of an internal online incident notification system in the hospital space, developed in the context of the institution’s Patient Safety Center. Methodology: The construction of the online system was divided into stages, the first being the definition of the construction of the internal online system based on the FormSUS interface. The next step is performed by a professional FormSUS forms manager, another named professional respondent, and a monitor. Responsible access respects the ethical precepts and the individual data identified, guaranteeing privacy and confidentiality. The form is restricted and can only be accessed at the invitation of the manager. Results and Discussion: The FormSUS form can be accessed through a shortcut that is displayed on all computers. The professional manager is the technician responsible for the creation and / or design of the structuring of forms, specific to meet the needs of the incident notification process. The respondent notifies the incidents through a shortcut that leads to the form itself, already structured, to send to the professionals of the Patient Safety Center. The content of each form and the tracking of your responses are the responsibility of the technical director of creating the form and his team. The form allows the inclusion of patient and incident data: full name of the patient; Medical history number; infirmary and bed; date of hospitalization; incidence date; age group; sex; description of the incident; identification of the notifier; contact, email and phone; office or function. Final considerations: The construction of an internal online incident notification system may represent greater agility in the detection and handling of incidents, greater adherence to notifications by professionals, in addition to improving security and quality actions in customer service patient.